Akibat Hukum Pencatatan Nikah Siri Sebagai Bentuk Perlindungan Hukum - Nofia Sari, Okta; Sari Damayanti, Andi; Hadrian, Reza (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
Marriage is a right granted by the 1945 Constitution to carry out and continue offspring. The marriage law is one of the most widely applied aspects of Muslims around the world compared to the laws of muamalah. Marriage is mitsaqan ghalidan, a solid bond, which is considered valid when it has fulfilled the conditions and harmony of marriage. Marriage must be performed in accordance with its religion and must be registered in the state so that it is able to protect the rights arising from marriage. If the marriage is not registered, it will cause many problems in the future so that everyone should pay attention to the importance of marriage registration.